Different approaches in the study of urban form - Paulo Pinho (2009)
In recent years, the debate on urban morphology has been polarized by two different perspectives, the first developed within the International Seminar on Urban Form (ISUF), based on the Conzenian and the Muratorian traditions, and the second space.syntax developed particularly in University College London. Both approaches are being further developed in a wide international context. The first and the second parts of this paper describe the origins, main characteristics, and contributions of these approaches, which are illustrated by the authors on-going research on Oporto urban form in Portugal. The last part presents some suggestions for bridging the gap between theseapproaches.